Effect of Lubricant Starvation on the Tribo-Dynamic Behavior of Linear Roller Guideway - Parivash Soleimanian; Mahdi Mohammadpour; Hamid Ahmadian (Shock and Vibration)
This paper presents an experimentally validated numerical approach linear roller guideways considering coupled vertical and horizontal (feed) motions and taking into account lubricant starvation. The inlet starvation is considered by incorporating potential flow method. Results show that starvation has pronounced effect on the lubricant film thickness, friction, and applied load on contact by up to 32%. Localised pressure values may vary by up to 100%. The severity of starvation effect is frequency dependent. It is also revealed that the starvation effect can be controlled by the amount of preload on linear guideway.